The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamanetworkopen.2022.14273
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Intrapartum Epidural Analgesia and Risk of Autism Spectrum Disorder in Offspring

Abstract: IMPORTANCE There is conflicting evidence on the association between intrapartum epidural analgesia and risk of autism spectrum disorder (ASD) in offspring.OBJECTIVE To evaluate the association between intrapartum epidural analgesia and the risk of ASD in offspring. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study was conducted inOntario, Canada, using the health and administrative records of singleton live births by vaginal delivery between April 1, 2006, and March 31, 2014. Neonates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The results from the study by Murphy and colleagues 4 are timely and important because they replicate the negligible association measure between intrapartum epidural analgesia and ASD in a population with a possibly different confounding structure than in previous research. 6 As shown by Straub and colleagues, 6 the pooled hazard ratio for ASD across recent studies conducted in the US, Denmark, and Canadian provinces other than Ontario was negligible (10% increased hazard).…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…The results from the study by Murphy and colleagues 4 are timely and important because they replicate the negligible association measure between intrapartum epidural analgesia and ASD in a population with a possibly different confounding structure than in previous research. 6 As shown by Straub and colleagues, 6 the pooled hazard ratio for ASD across recent studies conducted in the US, Denmark, and Canadian provinces other than Ontario was negligible (10% increased hazard).…”
mentioning
confidence: 64%
“…Validation of outcome status is also crucial in establishing whether an exposure is associated with a particular outcome. In their work, Murphy and colleagues defined ASD as the presence of at least 1 relevant diagnosis code at hospital discharge, emergency department visit, or outpatient surgery or at least 3 diagnostic codes within the health insurance plan records. Furthermore, the authors applied an alternative ASD outcome definition to maximize the outcome specificity.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Recent observational studies have suggested that LNA may alter physiological functions in the developing brain and potentially lead to autism spectrum disorders. 3,4 Although the association between LNA and long-term neurodevelopmental disability remains controversial, 5,6 it is important to understand the potential effects of LNA on neonatal neurophysiological functions. May clinicians would agree that it is rational to predict long-term consequence from the short-term status.…”
Section: Introductionmentioning
confidence: 99%